Enhancing heat recovery efficiency in chimney exhaust systems using thermoelectric generators – Thermal modeling and parametric analysis - Obeida Farhat; Mahmoud Khaled; Jalal Faraj; Khaled Chahine; Farouk Hachem; Cathy Castelain (Unconventional Resources)
The rising demand for sustainable energy solutions has made the utilization of waste heat from industrial processes a priority. Thermoelectric generators present an effective method for recovering and converting waste heat into useable electrical energy, therefore enhancing energy efficiency and sustainability. This study presents a parametric study of thermoelectric generators for waste heat recovery from heating chimney exhaust. In order to investigate the impact of placing the thermoelectric generators at different locations, simplified thermal resistance modeling was performed. Performance metrics demonstrate that the positioning of the thermoelectric generator site can bring about major improvements including thermal resistance, generated power, temperature of water heated, and energy conversion efficiency, which ranged from 0.57 % to 5.6 %, depending on thermoelectric generators configuration and operating parameters. By positioning thermoelectric generators on the exterior walls of the exhaust pipe, close to the heat source, a significant amount of electrical power—up to 37.67 W—could be produced. Additionally, a parametric analysis was conducted on important operating parameters: the mass flow rate and input temperatures of the exhaust gas and water. The application of 6 different cases showed that Case 5 of thermoelectric generator modules, with ṁg = 0.25 kg/s, Tg,i = 390 °C, ṁw = 0.3 kg/s and Tw,i = 20 °C, was the optimal condition, based on observations. The results demonstrate notable advancements in power production and energy recovery, and includes clear recommendations for future research that will bring about a shift in the direction of sustainable industrial operations.